Kahoot!-assisted Quiz Team: Promoting Students’ Interest in Learning English - Hentasmaka, Daning; Utami, Laili Dwi (English Department, Universitas Negeri Surabaya, 2024)
Students’ interest in learning is believed to affect their learning readiness and achievement. Considering the importance of learning interests, the present study aimed to investigate the effect of combining Quiz Team and Kahoot! to promote students’ learning interests, especially in learning English. This study implemented a quasi-experimental design, especially a nonrandomized control group pretest-posttest design. Forty-four junior high school students were involved as the participants of the study in experimental and control classes. A questionnaire on students’ English learning interests was used to collect the data. The questionnaire consisted of twenty-five items with five answer choices in Likert scales. The data collected were analyzed by using Mann-Whitney U test. The result of the data analysis showed the Asymp. Sig. (2-tailed) value was .000 which indicated a significant difference on English learning interest between students in the experimental class, who were taught by using Kahoot!-assisted quiz team, and the control class, who were not. Further results also showed that the mean rank of English learning interest of students in the experimental class exceeded those in the control class (31.57 compared to 14.22).